A study on factors influencing organizational effectiveness among employees in Syarikat Air Johor Holdings Sdn Bhd, Mersing Branch. - Mad Lemon, Normaliza (2011)
Organizational effectiveness is important to the organization. It is because the organization that effectiveness will achieve their goals and their objectives in the period given. If the organization becomes more effective, that organization can increase their productivity and so, will increase the company sales. This research was conducted to determine the factors that influence organizational effectiveness at Syarikat Air Johor Holdings Sdn Bhd, Mersing branch. The main objective is to examine the factors that lead to organizational effectiveness at Syarikat Air Johor Holdings Sdn Bhd, Mersing branch. The sample size for this study is 150 respondents. The questionnaire comprised 62 items adopted from Organizational Effectiveness (The Metrus Group), Job Satisfaction (Paul E. Spector) and Organizational Citizenship Behaviour (Minnesota) survey instrument and the respondent were asked to express their opinion on the scale of 1-5 where (1) disagree strongly, (2) disagree somewhat, (3) neither, (4) agree somewhat, and (5) agree strongly in a five point likert scale instrument. The questionnaires were prepared in two versions that are in Bahasa Malaysia and English. Results showed that all the independent variables which are job satisfaction and five dimension of organizational citizenship behavior have a positive relationship with the dependent variable which is organizational effectiveness. The strong factors that influence organizational effectiveness were job satisfaction and also one of the dimensions for organizational citizenship behavior which is civic virtue. SAJH is needed to make sure all of their employees satisfied with their benefits provided and enjoy doing the job. The employees also must have organizational citizenship behavior in theirs elf to make sure the organization will become effective and achieve their objectives.